2004
DOI: 10.1890/02-4039
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Responses of the Kuparuk River Ecosystem to Phosphorus Fertilization

Abstract: A long-term stream fertilization experiment was performed to evaluate the potential eutrophication of an arctic stream ecosystem. During 16 years of summer phosphorus (H 3 PO 4 ) fertilization, we observed a dramatic change in the community structure of the Kuparuk River on the North Slope of Alaska. A positive response to fertilization was observed at all trophic levels with increases in epilithic algal stocks, some insect densities, and fish growth rates. After approximately eight years of P fertilization, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
242
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(257 citation statements)
references
References 52 publications
(69 reference statements)
11
242
2
2
Order By: Relevance
“…Most stream ecosystems are naturally nutrient limited, and small increases in a limiting nutrient can enhance primary production with cascading effects on consumers (Hart and Robinson 1990, Slavik et al 2004, Cross et al 2006. We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites.…”
Section: Invertebrate Densitymentioning
confidence: 68%
See 1 more Smart Citation
“…Most stream ecosystems are naturally nutrient limited, and small increases in a limiting nutrient can enhance primary production with cascading effects on consumers (Hart and Robinson 1990, Slavik et al 2004, Cross et al 2006. We found that nutrient levels were significantly enhanced in spring-fed rivers and probably contributed to increased invertebrate density at these sites.…”
Section: Invertebrate Densitymentioning
confidence: 68%
“…Similar correlations between spring-fed invertebrate assemblages and elevated food resources have been reported from both Spain and New Zealand Death 2004, 2006). Nutrient availability and productivity have also been shown to positively affect invertebrate population growth rates and carrying capacity in other stream ecosystems (Slavik et al 2004, Benstead et al 2005.…”
Section: Invertebrate Diversity and Community Compositionmentioning
confidence: 99%
“…-values in the treatment reach probably resulted from rapid biological uptake, as seen in other nutrient-addition programs in ultraoligotrophic waters (e.g., Schindler et al 2011). Slavik et al (2004) attributed lower NO 3 -concentrations in the P-enriched reach of the Kuparuk River, Alaska, to increased biological uptake. Nutrient uptake was supported by observed increases in chlorophyll accrual rates, which were significantly higher in the treatment reach than in the control reach during all years of this study.…”
Section: Nutrients and Chlorophyllmentioning
confidence: 99%
“…These studies have shown that concentrations of inorganic N and P are generally very low as compared to other streams (Peterson et al 1992;McNamara et al 2008) and that primary productivity is P limited (Slavik et al 2004). In-stream C fixation rates are several orders of magnitude lower than C inputs from the watershed (Peterson et al 1986).…”
Section: Study Areamentioning
confidence: 99%
“…1). For many years, the Arctic LTER project has been adding phosphate to this section of the Kuparuk to study the effects of fertilization on stream function (Benstead et al 2007;Slavik et al 2004;Peterson et al 1993). Our sampling point was located in the reference reach upstream of the fertilizer addition point.…”
Section: Study Areamentioning
confidence: 99%